7c-6=8c-11

Simple and best practice solution for 7c-6=8c-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7c-6=8c-11 equation:


Simplifying
7c + -6 = 8c + -11

Reorder the terms:
-6 + 7c = 8c + -11

Reorder the terms:
-6 + 7c = -11 + 8c

Solving
-6 + 7c = -11 + 8c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-8c' to each side of the equation.
-6 + 7c + -8c = -11 + 8c + -8c

Combine like terms: 7c + -8c = -1c
-6 + -1c = -11 + 8c + -8c

Combine like terms: 8c + -8c = 0
-6 + -1c = -11 + 0
-6 + -1c = -11

Add '6' to each side of the equation.
-6 + 6 + -1c = -11 + 6

Combine like terms: -6 + 6 = 0
0 + -1c = -11 + 6
-1c = -11 + 6

Combine like terms: -11 + 6 = -5
-1c = -5

Divide each side by '-1'.
c = 5

Simplifying
c = 5

See similar equations:

| (-3x+5)+(-8x+30)=90 | | 20x^3-25x=0 | | 2-4x=-2x+4 | | Log(7)0= | | 3(3+4x)=21 | | 42-8x=14+6x | | 108=-2(2+8v) | | 11x+9x=140 | | -9+-8(-9q+-8)= | | 7t-2t=20-4+9 | | -3x-6+9x=-4x+6 | | 4k+1+3k=-6 | | 6(2x+10)=72 | | 1.75+0.35=2.80 | | 3(1-2x)=-5(3x-2) | | 8x-4=19-3x | | 2(w+5)+2w=70 | | V=imh | | -3(x-6)=-3-3x | | 2(4v-6)-2v=-8+5v | | 4y-3y-1=8 | | 2x-8=2(x-5) | | 2(3x+5)+2(8)=112 | | 0.25p=30 | | -5=-7(x+3)-3x | | 91-(6x+15)=6(x+4)+x | | 7x+17-5x+17=6 | | 21-8=x | | 5x-30=5x+30 | | 2m-m=13+16 | | 0.3(-0.9+8x)=3.2x | | 0.15-0.03(x+2)=-0.01(3-x) |

Equations solver categories